Influencer Celebrification: How Social Media Influencers Acquire Celebrity Capital - Brooks, Gillian; Drenten, Jenna; Piskorski, Mikolaj Jan (Journal of advertising, 2021)
The digital age has given rise to new pathways for everyday individuals to accrue media attention, which can be translated into promotional endeavors. Such sociocultural currency is referred to as celebrity capital, which can be exchanged within the field of advertising through celebrity endorsements. Traditional celebrities acquire celebrity capital through institutional intermediaries such as sport, television, music, and movies. Research is needed to understand the unique process by which social media influencers (SMIs) acquire celebrity capital. We draw on interviews with 40 global advertising industry practitioners and influencers to better understand how influencers acquire celebrity capital in a saturated media landscape. Extending previous work on celebrity capital and influencer advertising, this study conceptualizes a process which we term influencer celebrification. Influencer celebrification is the process by which SMIs acquire celebrity capital within an interconnected advertising ecosystem. Empirical findings identify three types of practices in the influencer celebrification process: generative practices; collaborative practices; and evaluative practices. This study identifies the role of advertising practitioners in the influencer celebrification process and offers implications for advertising theory and practice.